Ultrasonic Tomography System For Liquid/Gas Flow: Frame Rate Comparison Between Visual Basic And Visual C++ Programming - Abdul Rahim, Ruzairi (Penerbit UTM Press, 2006)
In order to process and simulate a tomography system, it has been found that Visual C++ programming has an advantage one step ahead compared to Visual Basic programming. Besides having an ability of higher processing speed, Visual C++ also encapsulates an extended function compared to Visual Basic. Real-time simulation of ultrasonic tomography system applied to liquid and gas flow has been implemented by previous researcher using Visual Basic 6.0 software programming. The program was excellent but unfortunately, the processing speed was not fast enough. Therefore, Visual C++ is expected to achieve a higher processing speed than Visual Basic. The main purpose of this research is to construct and develop a tomogram for visualizing the liquid and gas flow using Visual C++ software. By using a suitable image reconstruction algorithm, the tomogram will be interfaced with a tomography measurement system and a personal computer using Keithley DAS-1802HC interfacing card. By using Visual C++ programming software, the results showed an improvement in the image reconstruction speed and therefore, a high-speed measurement of ultrasonic tomography system could be achieved.